Effect of Grape Temperature, Oxidation and Skin Contact on Sauvignon blanc Juice and Wine Composition and Wine Quality - Marais, J. (South African Journal of Enology and Viticulture, 2017)
Sauvignon blanc is one of the most important white wine cultivars grown in South Africa. It is well-known that climatic and viticultural factors have a major effect on Sauvignon blanc grape and wine composition and quality.  Of equal importance is the effect of production factors on Sauvignon blanc wine composition and quality. The purpose of this study was to evaluate the effect of such factors. Wines were produced from grapes from two regions that were stored overnight at 0°C and 20°C. Skin contact was conducted for 15 hours at these temperatures, with as well as without S02 addition prior to fermentation. Free-run juices were used as control. Settled juices were analysed for 2-methoxy-3-isobutylpyrazine (ibMP) and monoterpenes, and the corresponding wines also for ibMP, acetate and ethyl esters, total polyphenols and total flavanoids. The wines were sensorially evaluated for fruitiness and the typical green pepper/grassy aroma of Sauvignon blanc.  Grape temperature, skin contact, and oxidative and reductive conditions prior to fermentation affected some of the above-mentioned component concentrations and therefore wine quality. Generally, most component concentrations were increased by skin contact, while polyphenol and flavanoid concentrations were lower in wines produced oxidatively. It appeared that wines produced reductively from free-run as well as low temperature skin contact juices presented the highest quality.